ILRI 1999. Making the livestock revolution work for the poor - International Livestock Research Institute (International Livestock Research Institute, 2000)
This annual report takes as its theme the central challenge facing the institute and its partners at the start of the new millennium: making the livestock revolution work for the poor. It is a companion report to the institutes new strategic plan, which takes the revolution as its basis in determining how ILRI's programme should evolve in the first decade of the 21st century. The report begins and ends on a farm in central Ethiopia, whose mixed crop-livestock producers are just beginning to participate in the expanding dairy market of the country's capital, Addis Ababa. In between are explored the anatomy of the revolution - what has happened and what will happen to supply and demand for different livestock products in different parts of the world. Then the report discusses the implications for equity, the environment and human health. It then briefly reviews some of the policy, institutional and technological interventions that can ensure that the revolution has a 'benign' outcome